2009
DOI: 10.1111/j.1443-1661.2009.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTIVE VALUE OF ENDOSCOPY AND ENDOSCOPIC ULTRASONOGRAPHY FOR REGRESSION OF GASTRIC DIFFUSE LARGE B‐CELL LYMPHOMAS AFTER HELICOBACTER PYLORI ERADICATION

Abstract: Background: Some gastric diffuse large B-cell lymphomas have been reported to regress completely after the successful eradication of Helicobacter pylori. The aim of this study was to investigate the clinical characteristics of gastric diffuse large B-cell lymphomas without any detectable mucosa-associated lymphoid tissue (MALT) lymphoma that went into complete remission after successful H. pylori eradication. Patients and Methods:We examined the effect of H. pylori eradication in 15 H. pylori-positive gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…The efficacy of HP eradication for gastric pure DLBCL has remained unknown until recently, with the exception of several anecdotal case reports. In 2009, Tari et al reported that HP eradication achieved CR in four of 15 gastric pure DLBCL patients (14). Subsequently, promising results of HP eradication for gastric pure DLBCL were reported by two independent groups in 2012.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The efficacy of HP eradication for gastric pure DLBCL has remained unknown until recently, with the exception of several anecdotal case reports. In 2009, Tari et al reported that HP eradication achieved CR in four of 15 gastric pure DLBCL patients (14). Subsequently, promising results of HP eradication for gastric pure DLBCL were reported by two independent groups in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…After that review, three papers describing HP eradication for gastric high-grade B-cell lymphoma were published (8,9,14). In total, HP eradication has achieved CR in 65 of 108 (60.2%) cases involving either DLBCL (MALT) or gastric pure DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the most important factor in risk assessment remains the loco regional staging and EUS preserves a great importance due to the fact that it is able to indicate, with accuracy superior to other techniques, the precise loco-regional stage of disease and consequently the required treatment (Pavlović et al 2005). Indeed, PGL of MALT type, when confined to mucosa and sub-mucosa layers responds to HP eradication therapy without any need of chemotherapy, meanwhile DLBCL are usually treated as general disease with chemo-immuno-therapy, even if recent case reports indicated the regression of locally staged DLBCL after HP eradication (Montalban et al, 2001, Tari et al, 2009. Independently from the stage and dissemination, transformation to DLBCL occurs in about 10% of the cases (Zucca et al, 2008 The GIT NHL 02/96 study, confirming the results of the previous study GIT NHL 01/92, revealed that surgery is no longer the better strategy in early-stage low-and high-grade gastric lymphomas (Koch et al, 2005), except when perforation, bleeding or obstruction take place, proving these findings in a cohort of 363 patients.…”
Section: Prognostic Assessment and Treatment: How Endoscopic Ultrasoumentioning
confidence: 99%